Proceedings of the International Conference on Defects in Semiconductors - International Conference on Defects in Semiconductors (16th : 1991 : Bethlehem, Pennsylavania); Davies, Gordon; Gary, G.; Stavola, Michael (Zurich : Trans Tech Pub, 1992)
40